Medical Image Enhancement Based on HVC - Ke, Li; Wang, Rui; Wang, Xu; Tian, Runlan (2007 1st International Conference on Bioinformatics and Biomedical Engineering, 2007)
Medical image enhancement is to process the image so that the result is more suitable than the original image for analysis and diagnosis. The information of image is acquired by the observer's eyes, so in the image processing, the human visual characteristics (HVC) as an important factor should be well thought of. In the paper, we study HVC from testing the distinguishability of gray scale and the sensitivity to the structure of image, analyze the physiological character and psychological characters of human vision, and summarize the laws of HVC. A new medical image enhancement method is presented based on HVC. It divides the image into the smooth areas and detail areas, and uses different processing methods for the areas according to HVC. Experiment results demonstrate that the method enhances the edge detail information, and improves the image quality, thereby increases the veracity of diagnoses, makes the treatment approach more exact.